Facilitating memory-based lie detection in immediate and delayed interviewing: The role of sketch mnemonic - Izotovas, Aleksandras; Vrij, Aldert; Strömwall, Leif A.; Mann, Samantha (Psichologija, 2020)
Memory enhancing techniques, or mnemonics, are typically recommended in evidence-based investigative interviewing guidelines. In the current study, the use of a sketch mnemonic and its effect on the responses of truth tellers and liars was examined. Participants (n = 49) watched a mock intelligence operation video. They were instructed to tell the truth or lie about this operation in an interview immediately afterwards, and again after a two-week delay. In both interviews, participants were requested to make a sketch of the place of the mock operation, and then to verbally describe the drawing. Results revealed that truth tellers reported more visual, spatial, temporal, and action details than liars in the immediate interview. Truth tellers also reported more spatial, temporal and action details than liars in the delayed interview. Truth tellers experienced a decline in reporting action details after the delay, whereas liars did not show a decline in reporting any details over time. Thus, truth-tellers showed patterns of reporting indicative of genuine memory decay, whereas liars produced patterns reflecting a ‘stability bias’. Between-statement consistency was not different across veracity conditions.